2018
DOI: 10.1111/aogs.13514
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status in Danish women with polycystic ovary syndrome: A register‐based cohort study

Abstract: | INTRODUC TI ONPolycystic ovary syndrome (PCOS) can be diagnosed in around 10% of premenopausal women. 1,2 PCOS is characterized by irregular menses, polycystic ovaries and hyperandrogenism. 1 Quality of life may be impaired in PCOS and the risk of depression and development of medical and psychiatric diseases is increased. 3,4 More than 50% women with PCOS are obese. 5 Obesity is associated with a more severe PCOS phenotype including more irregular menses, infertility and hirsutism, 6,7 and obesity is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
15
1
Order By: Relevance
“…To our knowledge, only one study has evaluated retirement among women with PCOS, as one dimension of socioeconomic status. This large Danish population study ( 13 ) had a cross-sectional, clinically rooted case–control design and reported that women with PCOS retired more often than non-PCOS women ( n = 870, 6% vs n = 1529, 4%, respectively). Our results, presenting cumulative risks in a total population sample, extend this evidence by showing that women with PCOS have an increased risk for early disability retirement compared to women without the condition (15.4% vs 8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one study has evaluated retirement among women with PCOS, as one dimension of socioeconomic status. This large Danish population study ( 13 ) had a cross-sectional, clinically rooted case–control design and reported that women with PCOS retired more often than non-PCOS women ( n = 870, 6% vs n = 1529, 4%, respectively). Our results, presenting cumulative risks in a total population sample, extend this evidence by showing that women with PCOS have an increased risk for early disability retirement compared to women without the condition (15.4% vs 8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only one study that has addressed this issue – albeit indirectly – by evaluating the association between PCOS and occupation-based socioeconomic status (SES) ( 13 ). This large, cross-sectional Danish study found that women with PCOS (aged 25–60) were more often unemployed or on welfare and had retired early than non-PCOS women.…”
Section: Introductionmentioning
confidence: 99%
“…This could probably be one of the reasons for the poor health and dietary pattern we studied in clinical parameters due to lack of education of women experienced low socio-economic status. [28,29]…”
Section: Discussionmentioning
confidence: 99%
“…The association between socio-economic status and PCOS is likely to be complicated, if poor psychological health is a feature of the condition as our data suggest, since this affects engagement with schooling, further study, employment and careers ( Lagerveld et al , 2010 ; Finning et al , 2019 ). A Danish study of socio-economic factors and PCOS considers the further complexity of migration and ethnic background in relation to socio-economic status ( Rubin et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%